2017
DOI: 10.1161/jaha.116.005426
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Intracoronary Morphine in ST‐Segment Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention: A Prospective, Randomized Trial

Abstract: BackgroundA cardioprotective role of morphine acting via opioid receptors has been demonstrated, and previous preclinical studies have reported that morphine could reduce reperfusion injury and myocardial infarct size in a way similar to that of ischemic periconditioning. This study aimed to evaluate the effect of intracoronary morphine on myocardial infarct size in patients with ST‐elevation myocardial infarction undergoing primary percutaneous coronary intervention.Methods and ResultsThis study was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Gwag et al, 2017 (28) Amostragem: 91 pacientes. Metodologia: pacientes com infarto do miocárdio com supradesnivelamento do segmento ST no ECG foram divididos em grupo controle (solução salina) e morfina, ambos pós intervenção coronária percutânea, proporção 1:1.…”
Section: Tabela 1 Autor Amostragem E Metodologia Resultadounclassified
See 1 more Smart Citation
“…Gwag et al, 2017 (28) Amostragem: 91 pacientes. Metodologia: pacientes com infarto do miocárdio com supradesnivelamento do segmento ST no ECG foram divididos em grupo controle (solução salina) e morfina, ambos pós intervenção coronária percutânea, proporção 1:1.…”
Section: Tabela 1 Autor Amostragem E Metodologia Resultadounclassified
“…Além deste cenário importante frente a inibição da agregação, o resultado de pesquisas deste campo tem mostrado que o efeito isolado da morfina, em aplicação durante terapia de intervenção coronariana percutânea, não apresenta melhora no padrão do infarto, tendo um mesmo espectro de musculatura cardíaca isquemiada, associado à ausência de mudanças nos picos de CK-MB, bem como semelhança de tempo de resolução do supra desnivelamento do segmento ST para grupos que utilizam ou não a morfina. Isso demonstra que o potencial de sobrevida para esse paciente não melhora com a analgesia (28) .…”
Section: Tabela 1 Autor Amostragem E Metodologia Resultadounclassified
“…However, another randomized controlled trial demonstrated that morphine did not show the preventive effect of myocardial salvage. They suggested that morphine use is associated with a slower uptake, delayed onset of action, and diminished effects of oral antiplatelet agents [ 33 ]. We demonstrated that intravenous morphine use during primary PCI did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sepsis, miRNAs can upregulate the expression of miRNA-155, enhance the release of inflammatory factors and inhibit the synthesis of anti-inflammatory factors (15). In the pathophysiological process of sepsis, miRNAs can promote the synthesis of inflammatory factors, enhance immune function, induce the apoptosis of immune cells and induce immunosuppression (16). miRNAs are involved in the precise regulation of the genesis, development and outcome of sepsis at various levels, such as the inflammatory response, immune cell differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in the precise regulation of the genesis, development and outcome of sepsis at various levels, such as the inflammatory response, immune cell differentiation and apoptosis. It is speculated that these miRNAs may possess regulatory effects on the differentiation of the effector T-cell (16). Thus, the present study next determined that overexpression of miRNA-200a-3p promoted the levels of IL-1β and IL-18 in vitro .…”
Section: Discussionmentioning
confidence: 99%